Insights from Exploration of Engaging Technologies to Teach Reading and Writing: Story Baker - Pahud, Michel (CPTTE 2016: Conference on Pen and Touch Technology in Education, 2016)
To engage children in learning to write, we spent several years exploring tools designed to engage children in creating and viewing stories. Our central focus was the automatic generation of animations. Tools included a digital stylus for writing and sketching, and in some cases simple robots and tangible, digitally-recognized objects. In pilot studies, children found the prototypes very engaging. In 2007 a decision not to develop new hardware was made, but at today’s greatly reduced tablet cost and with more capable touch and pen technology, these experiments could inspire further research and development. Related documents: List of Macro-Actions Visual Sentence - Code Documentation